1997
DOI: 10.1093/humrep/12.9.1955
|View full text |Cite
|
Sign up to set email alerts
|

The effect of follicle stimulating hormone therapy on human sperm structure (Notulae seminologicae 11)

Abstract: The effects of follicle stimulating hormone (FSH) treatment on the quality of human spermatozoa were assessed by examining the ultrastructure and the function of infertile human spermatozoa using a previously-defined formula. Using the spermatozoa as an andrological monitor shows that the therapeutic effect of FSH depends on the type of sperm defect. The response to FSH is, in many cases, positive and can be evaluated by examining the state of the ejaculated spermatozoa. From an initial group of 81 patients, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 0 publications
2
50
1
2
Order By: Relevance
“…Sakkas and colleagues previously reported the high occurrence of the cell surface protein Fas, in the ejaculates from patients with abnormal semen parameters [Sakkas et al 1999]. Apoptosis-like features other than the Fas ligand have also been observed in sperm including ultrastructural defects such as irregular, enlarged or fragmented nuclei with fragmented or marginated chromatin, cytoplasms with aggregated organelles, alteration in mitochondrial integrity, the presence of Bcl-x, caspases and p53 [Baccetti et al 1997;Donnelly et al 2000;Gandini et al 2000;Sakkas et al 2002;Weng et al 2002]. Clear evidence linking DNA fragmentation as shown by TUNEL to these features has not been presented [Muratori et al 2006].…”
Section: Abortive Apoptosismentioning
confidence: 98%
“…Sakkas and colleagues previously reported the high occurrence of the cell surface protein Fas, in the ejaculates from patients with abnormal semen parameters [Sakkas et al 1999]. Apoptosis-like features other than the Fas ligand have also been observed in sperm including ultrastructural defects such as irregular, enlarged or fragmented nuclei with fragmented or marginated chromatin, cytoplasms with aggregated organelles, alteration in mitochondrial integrity, the presence of Bcl-x, caspases and p53 [Baccetti et al 1997;Donnelly et al 2000;Gandini et al 2000;Sakkas et al 2002;Weng et al 2002]. Clear evidence linking DNA fragmentation as shown by TUNEL to these features has not been presented [Muratori et al 2006].…”
Section: Abortive Apoptosismentioning
confidence: 98%
“…Sakkas and colleagues suggested that "abortive apoptosis" may be the cause since abnormal human spermatozoa presented some apoptotic-like features (Sakkas et al, 1999). Further investigation led to the demonstration that other biomarkers of apoptosis in sperm cells were present such as BCL-X, TP53, caspases, in addition to diverse structural defects (Baccetti et al, 1997;Donnelly et al, 2000;Gandini et al, 2000;Sakkas et al, 2002;Weng et al, 2002 Table 1. Summary of the single strand DNA repair pathways in mammalian cells (Ciccia and Elledge, 2010;Hoeijmakers, 2009;Martin et al, 2010;Mukherjee et al, 2010;Nouspikel, 2009;Robertson et al, 2009).…”
Section: Chromatin Remodeling Processmentioning
confidence: 99%
“…This method is only used by our laboratory, but it is validated by the large amount of paper published in the last 10 years. A software to elaborate TEM data has been developed and it was used by other groups, who collaborated with us [11].…”
Section: Case Reportmentioning
confidence: 99%